Is There Too Much Benchmarking in Asset Management? - Kashyap, Anil K; Kovrijnykh, Natalia; Li, Jian; Pavlova, Anna (American Economic Review, 2023)
We propose a tractable model of asset management in which benchmarking arises endogenously, and analyze its welfare consequences. Fund managers' portfolios are not contractible and they incur private costs in running them. Incentive contracts for fund managers create a pecuniary externality through their effect on asset prices. Benchmarking inflates asset prices and creates crowded trades. The crowding reduces the effectiveness of benchmarking in incentive contracts for others, which fund investors fail to account for. A social planner, recognizing the crowding, opts for contracts with less benchmarking and less incentive provision. The planner also delivers lower asset management costs. (JEL D82, D86, G11, G12, G23, G41)